Diabetes, Hypertension, Obesity, and Smoking as Risk Factors for Chronic Kidney Disease in Productive Age - Rahmawati Sinusi; Arief Hargono (Universitas Airlangga, 2021)
Background: Based on the Indonesia basic health research report in 2018, the prevalence of chronic kidney disease (CKD) in the productive age group in Indonesia had increased from the previous year, to 1.97%. This condition can cause various complications that contribute to the high morbidity, which affects quality of life and productivity, so risk factors for CKD need to be understood to prevent the occurrence of the disease. Purpose: This study aimed to analyze the risk factors associated with CKD in the Indonesian productive-age population. Method: This study used data sourced from Indonesian Family Life Survey 5 (IFLS-5) with a cross-sectional research design. The study population was composed of all Indonesian residents who were respondents of IFLS-5. The research sample was made up of respondents aged 15–64 for whom complete information was available. The sample size was 29,120 respondents. The variables analyzed in this study were diabetes, hypertension, obesity, smoking, and CKD. The analysis method used was the chi-square test. Results: Bivariate analysis showed a significant relationship between CKD and diabetes (p = 0.01; prevalence ratio [PR] = 2.71; 95% CI = 1.74–4.22), hypertension (p = 0.01; PR = 2.62; 95% CI = 2.08–3.30), obesity (p = 0.01; PR = 1.67; 95% CI = 1.25–2.23), and smoking (p = 0.01; PR = 1.43; 95% CI = 1.17–1.75) in the productive age group in Indonesia. Conclusion: Diabetes, hypertension, obesity, and smoking have a significant relationship with CKD in the productive age group in Indonesia.